Efficacy and safety of electroconvulsive therapy plus medication versus medication alone in acute mania: A meta-analysis of randomized controlled trials. (August 2021) - Zhang, Jian; Wang, Guojun; Yang, Xi; Gao, Keming
Highlights: Eleven Chinese and one Indian RCTs were included for a meta-analysis. ECT combined with medication outperformed medication alone in reducing acute manic symptoms. This superiority occurred from after the first-week treatments or the 3-5 ECT sessions and onwards. ECT combination was as safe and tolerable as medication alone in acute mania, but had significant cognitive impairment. The generalization of the results of this meta-analysis is limited by high heterogeneity among included studies. Abstract: Although some studies have reported the potential efficacy of electroconvulsive therapy (ECT) in the treatment of acute mania, there is no consensus on the matter. Therefore, we performed a meta-analysis to determine the efficacy and safety of ECT combination with medication (ECT-combo) vs. medication alone (Med-alone) in the treatment of acute mania. Randomized controlled trials (RCTs) of ECT-combo versus Med-alone in acute mania were searched in Chinese databases and English databases from their inceptions up to February 2020. Twelve RCTs (including 863 patients, n=863) met our criteria and were included into meta-analysis. The pooled results found that ECT-combo outperformed Med-alone in reducing manic symptoms from baseline to endpoint with a standardized mean difference of -3.50 (95% CI: -4.57, -2.44, p<0.00001). The significant difference occurred after 3-5 treatments or after a 1-week treatment. ECT-combo had significantly increased memory impairment compared to Med-alone. Apart from increased memory impairment in ECT-combo group (SMD=8.33; 95% CI: 2.73 to 25.45, p= 0.0002), no other statistically significant differences in side effects or drop-out rates were found between groups. The results of this meta-analysis suggest that ECT-combo was significantly superior to Med-alone in efficacy and well-tolerated as Med-alone in the acute treatment of mania. However, larger studies with randomized, double-blind design, and standardized treatment regimens are still warranted due to the high heterogeneity of studies included in the present meta-analysis.